Precision public health: A natural experiment on chronic high-contrast PM2.5 exposure and pulmonary function among older adults - Hari Krismanuel; Purnamawati Tjhin (PLoS ONE, 2026)
Background: While fine particulate matter ( PM 2.5 ) is a respiratory hazard, most studies lack the temporal depth to distinguish chronic from acute effects, particularly among vulnerable older adults. This natural experiment study employs with a 10-year stable residency filter. To our knowledge, it is among the first in Southeast Asia to evaluate the decadal impact of PM 2.5 exposure on highly selected healthy older adults. Utilizing a Precision Public Health (PPH) framework, we provide regional evidence in Southeast Asia to integrate a quasi-longitudinal approach for isolating chronic respiratory effects using standardized lung function ( GLI 2012 – z-scores, adjusted for Southeast Asian populations ). Methods: We conducted a natural experiment involving 101 non-smoking older adults (65–80 years; normal BMI) in Indonesia. This design compared populations with ≥10-year residency in contrasting environments : high-exposure urban (Kedoya) and low-exposure rural (Pangalengan). The decadal filter ensured temporal precedence . Spirometry included internal BTPS (Body Temperature, Ambient Pressure, Saturated with water vapor) compensation. Multivariable linear regression evaluated the association between exposure and Z-scores, adjusting for demographic and lifestyle covariates. Results: High-exposure participants had significantly lower FEV 1 _z and FVC_z than the low-exposure group, with no significant difference in FEV 1 /FVC_z. Multivariable regression confirmed exposure group was the only independent predictor for FEV 1 _z (β = –1.42, p < 0.001) and FVC_z (β = –1.14, p < 0.001), after adjusting for covariates. These findings indicate a subclinical reduction in lung volumes consistent with a non-obstructive, restrictive spirometric pattern. Diagnostic testing indicated no violation of model assumptions was detected. Conclusions: High decadal PM 2.5 exposure is associated with significant standardized lung volume reductions. The 10-year residency stability criterion enhances causal inference . These findings advocate PPH approach, highlight the importance of z-score–based spirometric screening for early detection of subclinical pollution-related lung function decline. Integrating environmental risk assessment into geriatric care and air quality management offers a cost-effective pathway to mitigate long-term healthcare burdens in megacities.